Students’ Phonological Awareness and Their Strategy in Pronuncing Words - Tri Sekar Buana; Lalu Ari Irawan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The result of the study revealed that the students have difficulties in pronouncing words that wre categorized into three parts, those were consonant, vowel, and diphthong. In consonant, the students made errors /p/, /b/, /d?/, /z/, /f/, /v/, /d/, /s/, /r/, /k/, /?/, /t/, /ð/,/?/. In vowels, the students made errors /?/, /æ/, /e/, /?/, /?/, /?/, /i:/, /?/. In diphthong, the students made error /a?/, /??/, /??/, /??/, /a?/. Furthermore, the students’ strategy in their reading activity was categorized into three namely low, middle, and high categories. For low category, the strategy in reading activity was by checking the difficult word in a dictionary, asking the lecture how to pronoun the difficult word, and practicing to read the word continuously. For middle category, the strategy in reading activity was by doing repetition to every single word, listening the pronunciation of the words using u-dictionary, and always practicing to pronounce every single word. For high category, the strategy in reading activity was guessing based on their knowledge pronunciation and make a relation with the word that the same sounds.